2019
DOI: 10.1038/s41598-019-39609-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cannabinoids in hair after cosmetic application of hemp oil

Abstract: The detection of cannabis constituents and metabolites in hair is an established procedure to provide evidence of exposure to cannabis. We present the first known evidence to suggest that applying hemp oil to hair, as cosmetic treatment, may result in the incorporation of Δ 9 -tetrahydrocannabinol (THC), cannabinol (CBN), cannabidiol (CBD) and in one instance, the metabolite 11-hydroxy-Δ 9 -tetrahydrocannabinol (THC-OH). 10 volunteers treated their head hair daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“… 105 Hair growth abnormalities include lack of hair growth (alopecia), and excessive hair growth (hirsutism and hypertrichosis). Given the success of topically applied compounds to treat hair loss 106 coupled with the detection of major cannabinoid compounds in hair fibers, including CBD, following cannabis consumption 107 and topical application of hemp oil 108 further understanding of how cannabinoid compounds can potentially benefit hair-related issues is needed. 109–111 …”
Section: Introductionmentioning
confidence: 99%
“… 105 Hair growth abnormalities include lack of hair growth (alopecia), and excessive hair growth (hirsutism and hypertrichosis). Given the success of topically applied compounds to treat hair loss 106 coupled with the detection of major cannabinoid compounds in hair fibers, including CBD, following cannabis consumption 107 and topical application of hemp oil 108 further understanding of how cannabinoid compounds can potentially benefit hair-related issues is needed. 109–111 …”
Section: Introductionmentioning
confidence: 99%
“…A study in the UK showed that using hemp oil to cosmetically treat hair can lead to the absorption of THC, cannabidiol (CBD), cannabinol (CBN), and, on rare occasions, even the metabolite 11-hydroxy-delta-9-tetrahydrocannabinol (THC-OH) [8]. This study also demonstrated that when volunteers applied hemp oil to their hair, 89% were found to have absorbed one or more constituents of cannabis, while 33% had absorbed the three major constituents, namely, CBD, THC, and CBN [8]. Moreover, in their study of (self-reported) heavy cannabis users, Taylor et al found that 77% had traces of THC in their hair, 73% had CBN, and 19% had CBD [17].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, hemp oil is offered on the market as a cosmetic hair treatment, with product manufacturers claiming that the direct application of the oil can moisturise and protect hair, promote hair growth, and repair damaged hair. Despite the lack of scientific evidence supporting these claims, numerous online outlets sell these products, which range in composition from pure hemp oil to shampoos and similar hair treatments containing lower concentrations of hemp oil [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cannabinoids cannabinol (CBN) and cannabidiol (CBD) are also analysed in hair analysis [9]. These substances are not psychoactive and are THC oxidation products.…”
Section: Current Status 21 Chemical Structure Of Cannabismentioning
confidence: 99%